Determinants of Profitability Performance of Sugar Manufacturing Companies in Ethiopia - BahiruTesfaye (My University, 2015)
The main objective of this study was to examine the determinants factors of profitability of Ethiopia sugar manufacturing companies. The researcher collected quantitative data from financial statements covering a period of 2002-2013 for 3 sugar manufacturing companies in Ethiopia. The researcher used explanatory research design in this study and profitability was measured in terms of return on assets (ROA). Profitability is dependent variable, whereas current ratio, debt ratio, firm size, non-debt Tax shield, average collection period, inventory conversion period, cash conversion cycle, growth rate, inflation and growth domestic product are independent variables. The study used descriptive statistics and balanced fixed effect panel regression to analyze the data. The findings of the study showed that current ratio (CR) and debt ratio (DR) has significant positive relationship with profitability while, gross domestic product (GDP) has significant negative relationship with profitability
Keywords: Accounting